The positive effect of short-term nano-curcumin therapy on insulin resistance and serum levels of afamin in patients with metabolic syndrome - Nejat Kheiripour; Zahra Khodamoradi; Akram Ranjbar; Shiva Borzouei (Mashhad University of Medical Sciences, 2021)
Objective: Metabolic syndrome (MS) is a cluster of cardio-metabolic risk factors. MS is known as a highly prevalent disease worldwide. According to the existing evidence, consuming curcumin has positive effects on lipids profile, glucose, and body weight. This study aimed to evaluate the effects of nano-curcumin therapy on insulin resistance and serum level of afamin in patients with MS. Materials and Methods: Thirty MS patients (15 males and 15 females) received 80 mg/daily nano-curcumin for two months. The samples of fasting blood were collected from the participants at the beginning and 60 days after initiation of the intervention to measure biomarkers. Results: Comparing pre- and post-treatment with nano-curcumin values revealed a significant decrease in fasting plasma glucose (FPG) (p=0.017), insulin, homeostatic model assessment of insulin resistance (HOMA-IR) (p=0.006), and afamin (p=0.047). Moreover, there was a significantly negative relationship between afamin and high-density lipoprotein cholesterol (HDL-C) (p=0.044), as well as a significantly positive relationship between afamin and systolic (SBP) (p <0.001) and diastolic (DBP) (p <0.001) blood pressures. Conclusion: Results suggest that taking nano-curcumin for 60 days may have positive effects on afamin, FPG, insulin, and HOMA-IR in patients with MS, but would not significantly affect other metabolic profiles. More studies with larger sample sizes are required to confirm these findings.